2018
DOI: 10.1038/s41433-018-0206-0
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the predictors of needling after XEN gel implant

Abstract: Postoperative day 1 IOP is a predictor for needling in patients undergoing standalone XEN implantation. These results suggest that surgeons should not wait too long to intervene via needling if IOP in the early postoperative period is in the high teens or above. Type or severity of glaucoma did not influence the probability of needling or number of needling interventions required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 14 publications
0
27
0
4
Order By: Relevance
“…The need for both postoperative needling and 5-FU injections following XEN Gel Stent insertion is fairly well documented [ 15 ]. Specifically, in several prospective studies of XEN insertion with subconjunctival mitomycin-C needling rates have ranged from 30.7–43.2%, although it has been reported as low as 2.4% [ 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The need for both postoperative needling and 5-FU injections following XEN Gel Stent insertion is fairly well documented [ 15 ]. Specifically, in several prospective studies of XEN insertion with subconjunctival mitomycin-C needling rates have ranged from 30.7–43.2%, although it has been reported as low as 2.4% [ 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…[23] In a study to assess the predictors of needling post-XEN gel stent implantation, Midha et al reported that eyes with lower IOP on day 1 were less likely to require a needling procedure and that a significant association was seen between lower day 1 IOP and lesser number of post-operative needling procedures. [29] The probability of needling was up to 80% in patients having a postoperative day 1 IOP >20 mm Hg while this number decreased to 35% if the day 1 IOP was <10 mm Hg. However, no significant association was observed between day 1 IOP and needling interventions in phaco-XEN eyes.…”
Section: Bleb Revision/needlingmentioning
confidence: 97%
“…spowodowanego spadkiem lub z brakiem filtracji [13]. Zwraca bowiem uwagę fakt, że wbrew oczekiwaniom u znaczącego odsetka chorych leczonych tą metodą (32-47%) występuje konieczność wykonania needlingu lub chirurgicznej rewizji miejsca filtracji [11,15,21,23,24]. Ze względu na stosunkowo mniejszy i mniej burzliwy wypływ cieczy wodnistej pod spojówkę niż po zabiegach trabekulektomii, częściej dochodzi do obklejenia spojówką ostium zewnętrznego ujścia implantu.…”
Section: Rycinaunclassified
“…chirurgii minimalnie inwazyjnej (MIGS, minimally invasive glaucoma surgery) [5,[7][8][9]. MIGS została zdefiniowana przez Amerykańskie Towarzystwo Jaskrowe i FDA w 2014 r. jako: "procedury zwiększające odpływ cieczy wodnistej z oka, z zastosowaniem implantów lub bez, z dostępu z zewnątrz lub wewnątrz, wykonywane bez lub z minimalnym nacięciem twardówki" [10,11]. Zabiegi te mają może mniejszą skuteczność niż złoty standard chirurgii jaskry, ale za to większy profil bezpieczeństwa [5].…”
unclassified